2019
DOI: 10.17140/epoj-4-113
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Canine Rabies in Morocco: How to Make Pertinent Deductions for Control?

Abstract: This case control study aims to highlight risk factors to contract canine rabies, taking into account several factors like geographical affiliation, sex, age, season, socioeconomic and demographic characteristics of the environment in which the canine population evolves. Design Case-control study at national level in Morocco included non-randomized comparison groups. This approach was chosen to address practical considerations and the data used correspond to a five years period. A group of 215 cases and 215 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
1
4
0
Order By: Relevance
“…No association was found between rabies and age groups and sex. Our findings suggest that dog rabies is prevalent in all age groups which is in line with previous studies in nearby countries (Khayli M et al 2019, Yahiaoui, F.Z et al 2018) and elsewhere in the world (Douangngeun B et al 2017). Similarly, dog rabies was not gender specific (Ma, X et al 2020, Medley AM et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…No association was found between rabies and age groups and sex. Our findings suggest that dog rabies is prevalent in all age groups which is in line with previous studies in nearby countries (Khayli M et al 2019, Yahiaoui, F.Z et al 2018) and elsewhere in the world (Douangngeun B et al 2017). Similarly, dog rabies was not gender specific (Ma, X et al 2020, Medley AM et al 2017).…”
Section: Discussionsupporting
confidence: 93%
“…In contrast, the seasonality of rabies was demonstrated in several countries as in Peru (Lima district) (Malaga et al., 1979), Bhutan (South Asia) (Dhand & Ward, 2011) and even in neighbouring countries (Morocco and Algeria) (El Harrak, 2011; Khayli et al., 2019). Thus, the high number of dog rabies observed in a given season was explained by increased fighting between dogs during the breeding season, amplifying thus the risk of transmission of the disease (Yadav, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the seasonality of rabies was demonstrated in several countries as in Peru (Lima district) (Malaga et al, 1979), Bhutan (South Asia) (Dhand & Ward, 2011) and even in neighbouring countries (Morocco and Algeria) (El Harrak, 2011;Khayli et al, 2019).…”
Section: It Appears That Rabies Is Being Rarely Detected In Wildlife Inmentioning
confidence: 99%
“…In a previous study on animal rabies in Morocco, the dog's habitat and anthropogenic data were included as explanatory variables. The study found that suburban and rural habitats, public health management infrastructure (pounds, landfills, slaughterhouses, livestock markets), and road accessibility are determinant factors of rabies in Morocco [ 25 ]. This finding is supportive to the results of this study demonstrating the impact that human activities would have on the distribution of rabies in Morocco.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has shown that the suburb landscape is also starting to play a role in “recruiting” dog rabies cases, most likely because of the changes that begin to take place on the outskirts of cities [ 25 ]. The Suburb landscape becomes more « ruralized » due to cities's attractiveness (industrialization and rural exodus).…”
Section: Discussionmentioning
confidence: 99%